A Strange Case of Double Annular Pancreas - Nayak, Satheesha; Pamidi, Narendra; George, Bincy M; Guru, Anitha (JOP. Journal of the Pancreas, 2013)
Context The pancreas is a soft lobulated gland situated transversely across the upper part of the posterior abdominal wall. Its parts include the head, neck, body and tail. Annular pancreas is a rare condition where the head of the pancreas surrounds the second part of the duodenum like a ring. Case report We observed a rare type of double annular pancreas where the uncinate process encircled the third part of the duodenum. A process from the head of the pancreas encircled the junction between the first and second parts of the duodenum incompletely. There was a large artery running along the anterior border of the pancreas. The artery took origin from the superior mesenteric artery. Conclusion This case may be of interest to gastroenterologists and surgeons. Image: View of the duodenum and pancreas.